Mix Root Beet And Red Guava's Yogurt Impact On Eligible Women's Haemoglobin Level - Sari, Dewi Nurlaela; Mulyani, Yanyan; Rofiasari, Linda; Ariani, Antri; Yuliani, Meda; Lubis, Tika (Indonesian Operations Research Association (IORA), 2023)
Nutritional problems in children are closely related to the health and nutrition preparation of a woman to become a mother-to-be, in this case, eligle woman (15-49 year) who do not yet have a legal partner. The results of the Nutrition International survey in 2018 found cases of anemia in eligible wowen’s in West Java of 41.93%, this is in line with the target of giving blood supplement tablets to eligible women’s, especially the adolescent group, which is still low (25.2%) and still below the target of West Java (52%). There is a need for intervention efforts to prevent anemia by optimizing the provision of iron-containing foods in addition to giving iron tablets. The purpose of this research was to determine the effect of a mix of beetroot and red guava yogurt on hemoglobin levels in eligible woman. The method used is a quasi-experiment with a one-group pre-post design approach. The sample in this study was 30 respondents using a purposive sampling technique with the inclusion criteria of mild and moderate anemia, not having allergies to yogurt ingredients, and not being on medication disease that can cause anemia. Determination of anemia by measuring hemoglobin levels with the POCT (Point of Care Testing) method. The analysis technique uses frequency distribution, normality test, and bivariate test using Wilcoxon test through SPSS version 20.0 computer software. The results showed that all respondents (100%) experienced mild anemia before being given the yogurt mix of beets and red guava. There is a significant change with a pvalue of 0.000 < alpha value (0.05). It can be concluded that giving beetroot and red guava yogurt if consumed regularly and appropriately can reduce the incidence of anemia, so it is hoped that this can be used as a policy for intervention in eligible women’s with anemia.